Influence of self-efficacy and help-seeking on task value and academic achievement - Villavicencio, Felicidad T. (Philippine Journal of Psychology, 2011)
"Consistent with motivational models of help-seeking and self-regulated learning, this study examined the predictive relationships of help seeking, help avoidance, self-efficacy, task value, and achievement in final grades."